Simulation modelling of the phase behaviour of palm oil with supercritical carbon dioxide - Lim, Chee Siang; Abdul Manan, Zainuddin; Sarmidi, Mohamad Roji (Universiti Malaysia Sabah, Sabah, 2003)
The phase behaviour of crude palm oil (CPO) with supercritical CO2 was successfully modelled using the Redlich-Kwong-Aspen (RKA) thermodynamic model implemented in Aspen PlusÂ® 10.2.1 commercial simmulator. The procedure for modelling involves the estimation of pure component vapour pressure and critical properties, and the regression of phase equilibrium behaviour. The interaction parameters for the RKA model were obtained from the regression of experimental phase equilibrium data for palm oil component-supercritical CO2 binary system available in the literature. Using the temperature-dependent interaction parameters for each binary system, the RKA equation-of -state gives good correlations of the appropriate phase behaviour over wide ranges of conditions. The predicted palm oil component's distribution coefficients and solubilities showed good agreement with the experimental data reported in the literature. The simulated model provides an efficient and cost-effective alternative for the prelimanary design and optimization of the SFE process for complex CPO-supercritical CO2 system.